Anatomy of the vestibule of the omental bursa and epiploic foramen in the horse. (3rd April 2014) - Freeman, D. E.; Pearn, A. R.
Summary Reasons for performing study Epiploic foramen entrapment (EFE) is a common cause of colic in horses and available anatomical descriptions of this foramen and the associated vestibule of the omental bursa tend to be inconsistent, contradictory and inaccurate. Objectives To describe the anatomy of the vestibule of the omental bursa and epiploic foramen. Study design Dissection of 21 fresh equine cadavers shortly after euthanasia. Methods The anatomy of the vestibule of the omental bursa, epiploic foramen and related structures in the cranial abdomen were examined in situ and after removal from the abdomen. Photographs were taken and illustrations rendered to bring the relationship of the different folds, ligaments and organs involved into a 3D concept. Results The entrance into the vestibule and the passageway through it to the epiploic foramen is bounded by the gastropancreatic fold dorsally, caudally and ventrally. This fold constitutes the caudoventral boundary of the epiploic foramen along with the portal vein cranially and ventrally. The craniodorsal boundary of the epiploic foramen is formed by the caudate lobe of the liver. Conclusions The gastropancreatic fold plays a more important role in the anatomy of the vestibule of the omental bursa and the epiploic foramen than has been documented in the most widely used anatomy textbooks written in English. Because of the importance of EFE in horses, information from this study about the relevant anatomy could provide a first step towards improved methods for treatment and laparoscopic prevention of these diseases.